(untitled) (AYUSHDHARA, 2017)
Diabetes is a metabolic disorder which is affecting million people all over the world. Maharishi Charak described Prameharoga (20 types) ; and its one type is “Madhumeha ” having almost identical clinical feature of diabetes type II. Author taken detail review of available data for more than 2000 herbs and has collected various references/research work done by various scientist for pharmacological screening of anti-diabetic herbs through latest available In-vivo studies. And concluded 53 herbs have significant anti diabetic activity in different pharmacological in vivo model. Further for validation of modern research outcome authors had done extensive survey of most applicable herbal text book of Auyrveda“ Bhavprakash Nighantu” and Ayurvedic pharmacopeia of India part I volume I to VIII that has widely used by various stake holders of Ayurvedic industry, academia and students. Authors sorted about 25 Ayurvedic single drugs from reference mentioned above for their “Pramehaghna activity”. There is ample scope to trace out other single and compound drugs for cure of diabetes mellitus type II. Author’s also mentioned here some selected famous Ayurvedic compound and single drug that has been successfully used by Ayurvedic physicians in last 5 decades. Research community need to explore possibility to invent new drugs for management DM Type II like currently AYUSH 82(Developed by CCRAS & it has marketed in various trade name like right sugar, Diavit 82, DB6, IME 9) and BGR 34 (Developed by CSIR/NBRI) proven as very effective drug in the treatment of DM type II; hence research community of AYUSH system of medicines may explore the new era for NPD (new drug Development).